Scale and pattern of atrophy in the chronic stages of moderate-severe TBI - Green, Robin E.; Colella, Brenda; Maller, Jerome J.; Bayley, Mark; Glazer, Joanna; Mikulis, David R. (Frontiers in Human Neuroscience, 2014)
Background. Moderate-severe traumatic brain injury (TBI) is increasingly being understood as a progressive disorder, with growing evidence of reduced brain volume and white matter integrity as well as lesion expansion in the chronic phases of injury. The scale of these losses has yet to be investigated, and pattern of change across structures has received limited attention. Objectives. To measure (1) proportion of moderate-severe TBI patients with atrophy from 5 to 20 mos post-injury, and (2) relative vulnerability to and consistency of volume loss in structures with vulnerability to acute TBI. Methods. 56 patients (mean GCS = 6.1) underwent MRI 5 and 20 mos post-injury; 12 healthy controls underwent MRI twice. Mean monthly percent change was computed for whole brain (ventricle-to-brain ratio; VBR), corpus callosum (CC), and right and left hippocampi (HPC). Results. (1) Using a threshold of 2 z-scores below controls, 96% of patients declined on at least one region; 75% declined in at least 3/4. (2) There were no significant differences in proportion of patients showing decline across structures. For those showing decline in VBR, there was a significant association with both the CC and the right HPC (P < .05 for both comparisons). There were significant associations between those showing decline in (i) right and left HPC (P < .05); (ii) genu, body and splenium of the CC, and (iii) head and tail of the right HPC (P< .05 all sub-structure comparisons). Conclusions. Atrophy in chronic moderate-severe TBI is robust, and the CC, right HPC and left HPC appear equally vulnerable. Significant associations between the right and left HPC, and within substructures of the CC and right HPC raise the possibility of common mechanisms affecting associated regions, or spread of degeneration across structures (e.g., transneuronal degeneration). As atrophy has been associated with poorer functional outcomes, offsetting atrophy should be a target of rehabilitation interventions.